Investigation of Social Studies Prospective Teachers’ Motivation for Teaching Profession - Recepoğlu, Serpil; İbret, Bilgin Ünal (Journal of History Culture and Art Research, 2019)
In this study, it is aimed to determine motivation levels of social studies prospective teachers towards teaching profession. This is a descriptive research in survey model. The sample of the study consists of total . 2193 social studies prospective teachers of 1th 2nd 3th 4th grade at Education Faculty of 12 Universities in the 20142015 academic years.According to findings of this research, the perceptions of social studies prospective teachers’ motivation for teaching profession are high and agreeing. Social studies prospective teachers’ motivation for teaching profession shows a significant difference according to the gender of teacher candidates. Female prospective teachers ’perceptions are higher than male prospective teachers’ perceptions. Social studies prospective teachers’ motivation for teaching profession changes significantly according to grade level. Social studies prospective teachers’ motivation for teaching profession is at the highest level in the first grade, but it is the lowest level in the 4th grade. Social studies prospective teachers’ motivation for teaching profession does not differ significantly according to university.